Motive Development Training Program for Enhancing the Competitiveness of Semanggi Batik Products - Hardjati, Susi; Safeyah , Muchlisiniyati; Wahyudi, Kalvin Edo (Future Science, 2020)
This research has two objectives main. First, describe the motive development training program to increase the competitiveness of Semanggi Batik products. The program was intended for the craftsman batik semanggi to join the community self-help group (KSM) Semanggi 2 Sememi Village, Benowo District, Surabaya City. Through this program, it is hoped that the Semanggi Batik motif will be more varied and thus the product competitiveness will increase. The second objective is to analyze the effectiveness of the motive development training program. The effectiveness analysis was carried out by using a descriptive quantitative approach. Data were collected using a questionnaire to 20 respondents. The results of the analysis show three main things. First, the motive development training program is indeed needed by the training participants. This is shown in the perception score of the urgency of the material reaching 82.5% (very high). Second, it turns out that the ability of the participants in the development of the Semanggi Batik motif is only 30% (less fortunate). Third, the participants assessed the effectiveness of the training for motive development training at 83.33% (very high / very effective). Based on this analysis, it can be concluded that the KSM knowledge and skills improvement program in producing semanggi batik is very effective and worthy of being used as a model for batik development in other communities.